“CLIMATE CHANGE AND AGRICULTURAL SUSTAINABILITY: CHALLENGES AND ADAPTATION STRATEGIES” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Climate change is one of the most pressing global issues of the 21st century. It directly affects agriculture through rising temperatures, irregular rainfall, and frequent natural disasters. These changes reduce crop yields, harm soil quality, and threaten food security. At the same time, farmers are trying to adapt with sustainable practices such as water-saving irrigation, drought-resistant crops, and renewable energy. International cooperation and climate-smart farming are essential to protect rural communities and ensure long-term development.